DUKUNGAN ORANG TUA BAGI REMAJA KATOLIK DI TENGAH MASALAH KENAKALAN REMAJA - Wulandari, Agnes Astri; Wijaya, Albert I Ketut Deni (PERDIKKATI (Perkumpulan Pendidikan Keagamaan Katolik Indonesia), 2024)
Juvenile delinquency refers to such actions that violate laws as well as societal values. It is caused by unresolved internal conflicts within adolescents. Parental support is crucial for adolescents regarding to this unresolved conflicts. This research aims to empirically examine the parental support for Catholic adolescents related to the issue of juvenile delinquency. The study was conducted in the Rejoso Basic Chiristian Community of the St. Mary Parish, Blitar, focusing on Christian families with adolescent children. Respondents for this research were selected through purposive sampling. This technique allows the researcher to personally choose appropriate informants who are knowledgeable or have extensive information related to the researched issue. Data collection methods for this study included structured interviews and observation. Structured interviews used an interview guide consisting of questions formulated based on the research problems. The research results indicated that parental support for Catholic adolescents significantly influences their church life related to the current issues of juvenile delinquency. The role of parents in the religious education of adolescents in Catholic families in the digital era involves guiding, supervising, and supporting the adolescents. The presence of parents must be friendly and become a good role models for their teenagers.